Into the riverlands - Vo, Nghi (Vo, Nghi. Singing Hills cycle, 2022)
"The Empress of Salt and Fortune Wandering cleric Chih of the Singing Hills travels to the riverlands to record tales of the notorious near-immortal martial artists who haunt the region. On the road to Betony Docks, they fall in with a pair of young women far from home, and an older couple who are more than they seem. As Chih runs headlong into an ancient feud, they find themselves far more entangled in the history of the riverlands than they ever expected to be. Accompanied by Almost Brilliant, a talking bird with an indelible memory, Chih confronts old legends and new dangers alike as they learn that every story-beautiful, ugly, kind, or cruel-bears more than one face. The novellas of The Singing Hills Cycle are linked by the cleric Chih, but may be read in any order, with each story serving as an entry point"--